APLIKASI E-COMMERCE PAKAIAN BERBASIS ANDROID MENGGUNAKAN METODE PROTOTYPE - Emon Sulaksana; Ichwani, Arief; Anwar, Nizirwan; Setiawati, Popong (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
E-commerce is a profitable opportunity for SMEs, particularly in the sale of household goods like clothing. SMEs' growth in e-commerce has been driven by theCovid-19 pandemic, leading to widespread adoption ofe-commerce systems. OvintLevint, a clothing store thatstarted during the pandemic, still relies on traditionalmarketing methods like word-of-mouthrecommendations. This hampers their growth andcompetitiveness against well-known brands, requiringsignificant investment and time to overcome. Currently, OvintLevint accepts both cash and non-cashtransactions, including transfers and WhatsApp-basedpayment proofs. However, there are frequent instancesof lost transaction receipts and income recording errors. To facilitate customers and OvintLevint, an Android system is being developed for online product purchases. Equipped with a payment gateway, this system aims tosimplify customer transactions. The development usesprototyping with the Flutter framework (Dart andjQuery) for frontend, and Laravel framework (PHP andBootstrap) for backend and web administrationservices. Research findings suggest that developing a clothing e-commerce application can streamline theordering process, transaction data processing, andenhance marketing efforts.